Tingkat Pengetahuan Panitia Kurban Tentang Penyakit Lumpy Skin Disease di Kota Bandar Lampung - I K Habsari; V R Pertiwi; G G Maradon; J A Putritamara (PETERPAN (Jurnal Peternakan Terapan), 2023)
Lumpy Skin Disease (LSD) is transboundary disease and characterized by the presence of nodules on the skin This Study is aimed to assess the level of knowledge of the sacrificial committee towards Lumpy Skin Disease (LSD) in Bandar Lampung City. The data were taken by using research instruments (questionnaire) with 100 respondents. The Research subjects in this study were sacrificial committees in 20 districts around Bandar Lampung City. Sacrificial committees were dominated by 50-60 years old, level of education Senior High School, and 1-10 years experienced in becoming sacrificial committee. Results showed that the average level of respondents’ knowledge regarding the LSD symptoms is high (80), whereas the knowledge towards LSD transmission, and control are in the medium level (72.06 and 64.3)